Engineering Nano‐Therapeutics to Boost Adoptive Cell Therapy for Cancer Treatment. Issue 5 (23rd February 2021) - Zheng, Chunxiong; Zhang, Jiabin; Chan, Hon Fai; Hu, Hanze; Lv, Shixian; Na, Ning; Tao, Yu; Li, Mingqiang
Abstract: Although adoptive transfer of therapeutic cells to cancer patients is demonstrated with great success and fortunately approved for the treatment of leukemia and B‐cell lymphoma, potential issues, including the unclear mechanism, complicated procedures, unfavorable therapeutic efficacy for solid tumors, and side effects, still hinder its extensive applications. The explosion of nanotechnology recently has led to advanced development of novel strategies to address these challenges, facilitating the design of nano‐therapeutics to improve adoptive cell therapy (ACT) for cancer treatment. In this review, the emerging nano‐enabled approaches, that design multiscale artificial antigen‐presenting cells for cell proliferation and stimulation in vitro, promote the transducing efficiency of tumor‐targeting domains, engineer therapeutic cells for in vivo imaging, tumor infiltration, and in vivo functional sustainability, as well as generate tumoricidal T cells in vivo, are summarized. Meanwhile, the current challenges and future perspectives of the nanostrategy‐based ACT for cancer treatment are also discussed in the end. Abstract : Nanotechnology has recently boosted adoptive cell therapy for cancer treatment. This review summarizes the emerging nano‐enabled approaches that design multiscale artificial antigen presenting cells for cell proliferation in vitro, promote transducing efficiency of tumor‐targeting domains, engineer therapeutic cells for in vivo imaging, tumor infiltration, and in vivo functional sustainability, as well as generate tumoricidal T cells in vivo.